বঙ্গবন্ধুর নির্বাচিত ভাষণ, চতুর্থ খণ্ড - খান, এ এইচ; ইসলাম, চৌধুরী এম সাইফুল (ঢাকা : বাংলাদেশ কালচারাল ফোরাম, 2011)
Collection of speeches of Sheikh Mujibur Rahman, 1922-1975, politician and former president of Bangladesh.
AAL
Keywords: Mujibur Rahman, -- Sheikh, -- 1920-1975 -- Political and social views; Bangladesh -- Politics and government